Analisis Keinginan untuk Pindah: Studi Empiris Pada KAP Besar di Jakarta Yang Berafiliasi Dengan KAP Asing (The Big Four) - JADONGAN SIJABAT (Jurnal Akuntansi Bisnis, 2011)
The purpose of this research is to examine the relationship of job satisfaction and organizational commitment to turnover intentions. Next, the purpose of this paper is to examine whether job satisfaction related to turnover intentions through organizational commitment. This research conducted with survey on auditors working on the big audit firms in Jakarta that affiliated to foreign audit firms (The Big Four). Unit analysis are auditors who have non-partner position i.e: junior, senior and manager that cOllcentrated in audit sen'ices. The structural equation modeling 'with AMOS program is used to analized the data. The results of this research suggest that organizational commitment has sign~fical1t negative relationship to turnover intentions. Job satisfaction has sign~ficant negative relationship to turnover intentions. Next, job satisfaction has sign~ficant positive relationship to organizational commitment. This result suggest that job satisfaction related to turnover intentions both of direct or through organizational commitment.